2017
DOI: 10.1038/srep45458
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mapping of the Helicobacter pylori NikR regulon provides new insights in bacterial nickel responses

Abstract: Nickel homeostasis is important for pathogenic and ureolytic bacteria, which use this metal ion as enzymatic cofactor. For example, in the human pathogen Helicobacter pylori an optimal balance between nickel uptake and incorporation in metallo-enzymes is fundamental for colonization of the host. Nickel is also used as cofactor to modulate DNA binding of the NikR regulator, which controls transcription of genes involved in nickel trafficking or infection in many bacteria. Accordingly, there is much interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
1
51
0
3
Order By: Relevance
“…32 Similar investigations using ChIP and RNA sequencing to systematically map the regulon of NikR revealed not only the known involvement of the Nickel regulator in metal homeostasis but also that NikR under nickel stimulation regulates virulence factors, toxin-antitoxin systems, and noncoding RNA. 33 Scavenging and controlling the homeostasis of nickel is of major importance for H. pylori, which both include the regulation of transporters and metal-binding proteins but also feedback loops regulating NikR itself. In contrast to HsrA, this study also revealed extensive intragenic binding by NikR.…”
Section: Helicobacter Pylori Gene Expressionmentioning
confidence: 99%
“…32 Similar investigations using ChIP and RNA sequencing to systematically map the regulon of NikR revealed not only the known involvement of the Nickel regulator in metal homeostasis but also that NikR under nickel stimulation regulates virulence factors, toxin-antitoxin systems, and noncoding RNA. 33 Scavenging and controlling the homeostasis of nickel is of major importance for H. pylori, which both include the regulation of transporters and metal-binding proteins but also feedback loops regulating NikR itself. In contrast to HsrA, this study also revealed extensive intragenic binding by NikR.…”
Section: Helicobacter Pylori Gene Expressionmentioning
confidence: 99%
“…To balance these opposing factors, H. pylori possesses a robust network of metalloregulation and nickel homeostasis systems, with the nickel-responsive transcription factor NikR playing a central role (11,12). H. pylori NikR (HpNikR) is an activator or repressor of a variety of genes encoding the urease precursor proteins as well as nickel transporters, nickel storage proteins, and others (13)(14)(15)(16)(17)(18). HpNikR enacts this activity via nickel-activated DNA binding to the corresponding promoters (18)(19)(20).…”
mentioning
confidence: 99%
“…Another study attempted to uncouple direct versus indirect transcriptional effects of the nickel-responsive repressor NikR using a short, high pulse of nickel and a combination of RNA-seq and ChiP-seq. 37 This analysis suggested that some genes previously attributed to the NikR regulon are secondary targets through upregulation of Fur and noncoding RNAs. While the authors generally argued that NikR was not a global regulator, as only a subset of previous targets confirmed that they were able to identify two new OMPs in the NikR regulon.…”
Section: Transcriptional Regulatorsmentioning
confidence: 92%
“…As motility is downregulated during biofilm formation, the authors suggested that this points to the importance of FliM in regulating additional cellular processes. Another study attempted to uncouple direct versus indirect transcriptional effects of the nickel‐responsive repressor NikR using a short, high pulse of nickel and a combination of RNA‐seq and ChiP‐seq . This analysis suggested that some genes previously attributed to the NikR regulon are secondary targets through upregulation of Fur and noncoding RNAs.…”
Section: Regulation Of Virulencementioning
confidence: 99%